Vapor-liquid equilibria for isobutane plus pentafluoroethane (HFC-125) at 293.15 to 313.15 K and+1,1,1,2,3,3,3-heptafluoropropane (HFC-227ea) at 303.15 to 323.15 K - Lee, BG; Park, JY; Lim, JS; Lee, YW; Lee, CH (AMER CHEMICAL SOC, 2000)
Isothermal vapor-liquid equilibria were determined for binary systems of pentafluoroethane (HFC-125) + isobutane (R600a) at 293.15, 303.15 and 313.15 K and 1,1,1,2,3,3,3-heptafluoropropane (HFC-227ea) + isobutane (R600a) at 303.15, 313.15 and 323.15 K in a circulation-type equilibrium apparatus. The experimental data were well correlated with the Peng-Robinson-Stryjek-Vera (PRSV) equation of state combined with the NRTL excess Gibbs free-energy model and Huron-Vidal original mixing rules.
Keywords: ALTERNATIVE REFRIGERANT MIXTURES; PHASE-EQUILIBRIA; STATE